Z‐Scheme Flower‐Like SnO2/g‐C3N4 Composite with Sn2+ Active Center for Enhanced Visible‐Light Photocatalytic Activity. (10th June 2021) - Bao, Zhiyong; Xing, Mengmeng; Zhou, Yu; Lv, Jun; Lei, Dangyuan; Zhang, Yong; Cai, Jing; Wang, Jiaheng; Sun, Zhenjie; Chen, Wenjuan; Gan, Xiaorong; Yang, Xingyu; et al.
Abstract: The invention of defect‐engineering motivated Z‐scheme photocatalytic complexes has been treated as an emerging opportunity to accomplish effective carrier separation and electron transfer in hybrid heterojunctions, contributing a novel approach to accomplish modified visible‐light driven photocatalytic performance compared to traditional nanocomposites. Exploring a desired carrier medium is crucial to support impressive electron transportation in Z‐scheme photocatalytic nanocomposites. Here, the role that the Sn 2+ /Sn 4+ redox couple plays in the photocatalytic process is systematically studied by taking the flower‐like SnO2 /layered g‐C3 N4 with deficient Sn 2+ reactive sites as an example, where the defect‐engineering can be introduced by heat treatment. The experimental results and computational simulations demonstrate that the deficient Sn 2+ reactive sites can facilitate small molecule adsorption and boost the interfacial carrier separation and transfer in the photocatalytic procedure by bringing in the Sn 2+ /Sn 4+ redox couple. This work provides a more in‐depth exploration of Z‐scheme photocatalytic‐system construction and is helpful to the development of defect‐engineering approaches with high photocatalysis performance. Abstract : Theoretical and experimental studies reveal that defective Sn 2+ active sites can boost small organic molecules adsorption and facilitate the interfacial charge separation/transfer in a Z‐scheme flower‐like SnO2− x /g‐C3 N4 photocatalytic system by introducing a Sn 2+ /Sn 4+ redox couple. This work provides a more in‐depth exploration of Z‐scheme photocatalytic‐system construction and is beneficial to the development of defect‐engineering approaches with designed photocatalysis performance.